Importance of reservoir simulation and early reservoir management for successful field development — Case study - Zeinab Zargar; Ganesh C. Thakur (Energy Reports, 2022)
The current RF (recovery factor) of the subject reservoir is <10%, considered uncharacteristically low for a high porosity and permeability reservoir. Detailed studies were conducted to find out the reasons behind the reservoir’s very low RF. Applying analytical tools, we learned that; (1) a bottom aquifer supported more than 70% of the reservoir energy, (2) excessive free gas production occurred, and (3) productivity of almost all the wells was deteriorated by water/gas coning. Multiple simulation runs were conducted to achieve a reasonable history matching of 47-year long field production and pressure profiles. Results show that initial oil–water and gas–oil contacts moved up considerably in the reservoir. Consequently, a significant gas cap re-saturation happened. This resulted in a very low RF and failure of several wells. These findings are in close agreement with the material balance results and log analysis. Nearly 40% of original oil-in-place moved into the initial gas cap which could have been prevented by controlling producing GOR (gas–oil ratio) and reservoir pressure, and close monitoring of fluid contacts.Alternative RM methodologies of reservoir were investigated showing that the RF could have been as high as 35%, utilizing four horizontal wells with an average horizontal section of about 800 m located in the middle of oil column, and controlling producing GOR. That proves that high oil recovery with significant economic benefits can be achieved by utilizing horizontal wells in development of the oil reservoirs with a large gas cap and strong aquifer. Finally, this study highlights the need of performing analytical analysis for a reservoir experiencing complex behavior prior to reservoir simulation study to get more reliable understanding of the reservoir behavior, establish consistency across the various datasets, and also provide initial field development planning insights.